THE RATIO OF MAUQUF HADITH AND COMPANIONS' IJTIHAD IN ISLAMIC LAW ISTINBATH - Wahyudin Darmalaksana (Khazanah Hukum, 2021)
This study aims to discuss the ratio of mauquf hadith and ijtihad of friends in the case of mut’ah marriage being forbidden. This research uses a qualitative approach with descriptive methods. The results of the research and discussion show that the ijtihad of Umar ibn al-Khathab's friend regarding mut’ah marriage is a mauquf haqiqi hadith as the ratio of ijtihad mutlaq mustaqil and is a famous mauquf hadith as the ratio of ijtihad jamai', and the ijtihad of Umar's friend is the atsar of the Prophet SAW. the mauquf lafdzi category which is marfu hukmi because it has the support of the Prophet's provisions. This study succeeded in concluding that there is a ratio between the mauquf hadith and the ijtihad of a friend in the case of Umar ibn al-Khatthab's ijtihad in the Shari'a prohibiting mut’ah marriage which is accepted as an argument for Islamic practice.